(3OjhGf GdTQja GdQVjs - (3eMeO Hf GdMSjf Hf ehSi GdYdhj GdMSjfj GdehShj, GdTQja GdQVj , CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3qMjjG Ohf GdcKjH eQJY GdXHj GdQHjH s
(3BNQgG (B:s
(3ef bUjOI ChdgG(B: (3OY ef OehYc HYO GdHjf ddOef ZOG dOGQge hGdjhe ddXYf hBNQgG(B: (3Thb Cde heG Thbj Edi CMO Shi ddPj fGe Yf djdi hCjbXfj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGdKI hdYdgG eNJGQGJ ef GdOjhGfs
(3hQOJ CjVkG JMJ Qbe (B2191(3, (B2244(3, (B70(3, (B725s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B128 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B794s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs